Creación del producto “Ruta de Ciclopaseos Vivenciales” para el desarrollo del turismo en el cantón Junín, Manabí, Ecuador - Intriago Macías, Lucía Concepción (2019)
The goal of this research is to design the product "Experiential Cycling Route" for the development of tourism in the canton of Junín, Manabí, Ecuador. The work has a mixed approach, uses theoretical methods of analysis and synthesis, and establishes a four-phase methodology. In the first phase, a situational tourism analysis is made oriented to identify the tourist supply, potentialities and problems in the territory through the use of the inventory technique of the MINTUR (2017), with the implementation of this technique, the tourism attractions inventory was updated. The strategic analysis of tourism reported scarce tourist facilities, lack of integrated and diversified tourism products; the low confidence of the population regarding the development of tourism for the improvement of their quality of life linked to the fact that in Junín tourism sector is not considered as a governmental priority. The second stage implies a tourism market study focused on the analysis of the demand, competition and tourism trends; primary sources of information are confronted, surveys are processed through the statistical tool SPSS; the market is segmented and it is found that Junín is considered a transit city; the type of tourism developed is mainly familiar. The third phase outlines a strategic plan for the creation of the tourist product "Experiential Cycling Route for the Junín canton"; the results of this research enabled the identification of four routes, three of them for adventure and extreme cycling; and the experiential cycling proposal for which a brand was created. The fourth phase is the validation of experts on the relevance in the creation of the "Experiential Cycling Route” which verified that the consistency between their opinions is strong, and it is also confirmed that the product shows as main characteristics: accessibility for anyone, applicability, feasibility, impact and benefit to the communities.